Bispectral Analysis of Needle EMG Signals to Detect Differential Patterns of Muscle Activity in Radiculopathy Patients - Fariba Biyouki; Saeed Rahati; Katri Laimi; Ali Shoeibi; Reza Boostani (Iran, Islamic Republic of, 2025)
Radiculopathy refers to a set of conditions, in which one or more nerves is affected and does not work properly. The emphasis is, however, on the nerve roots. In addition, L5 radiculopathy is the most common radiculopathy encountered in electrodiagnostic laboratories. Needle electrode examination is known to be the most effective diagnostic tool for this disorder. The objective of the present study was to quantify muscular changes in radiculopathy patients, using needle EMG signals recorded from tibialis anterior muscle of a healthy man without a history of neuromuscular disease and a man with neuropathy due to L5 radiculopathy. Moreover, this paper investigated the utility of HOS analysis by examining bispectral patterns and extracting features based on amplitude and phase of the bispectrum for identifying the differences. The results showed that the mean value of amplitude based features were higher in patient compared with those of healthy control. However, phase entropy indicated a reduction in radiculopathy patient. In addition, bispectral magnitude contour plots enabled us to visually differentiate muscle activities.
Congress publication: 5th Iranian Conference on Electrical and Electronics Engineering (ICEEE2013)